Triazole‐Functionalized Norbornadiene‐Quadricyclane Photoswitches for Solar Energy Storage. Issue 32 (16th August 2018) - Petersen, Anne U.; Jevric, Martyn; Moth‐Poulsen, Kasper
Abstract : Herein work on 2, 3‐substituted norbornadiene‐quadricyclane molecular photoswitches designed for solar energy storage purposes is presented. A series of six new systems bearing 1, 4‐ or 1, 5‐alkyl triazoles as the acceptor unit combined with various aryl donor groups, as well as four functional intermediates, were synthesized and fully characterized. The new photoswitches were evaluated by measuring optical absorption profiles, activation energies for the thermal conversion of quadricyclanes to norbornadienes, as well as the storage energy densities. These triazoles featured a molar energy storage of 81.2–101 kJ mol –1 corresponding to energy densities of 215–267 kJ kg –1 . The optical absorption profiles exhibited absorption onsets up to 382 nm and a study of the thermally activated conversion from high‐energy quadricyclanes to norbornadienes revealed energy storage half lives of up to 402 days at 25 °C. The modular nature of the "click chemistry" synthesis concept used herein enables access to a large range of compounds with tailored properties such as solubility, thermal half‐life, and solar spectrum match. Abstract : A series of norbornadiene‐quadricyclane molecular photoswitches bearing 1, 4‐ or 1, 5‐alkyl triazoles combined with various aryl donor groups were synthesized and fully characterized. The new photoswitches were evaluated for possible future use in solar energy storage. The modular nature of the "click chemistry" synthesis concept used herein enables access to a large range of compounds.